Public Accountability and its Diverse Context: a Tale from Different Disciplinary Parameters. - Basheka, Benon (Kabale University, 2023)
One of the greatest hurdles of sound administrative and governance contexts in Africa remains that of accountability. Accountability in itself is huge and can be seen from different angles and no issue of a journal like this one can pride of a capacity to cover all forms of accountability. There is political accountability, financial accountability, administrative accountability, managerial accountability, and professional accountability. Accountability can also be business accountability, bureaucratic accountability, social accountability, representational accountability, audit accountability, fiscal accountability, legal accountability and many other forms. There remains a serious deficit of all these forms in the African continent. In all forms of accountability there are four outstanding pillars. Keywords: Public Accountability, Diverse Context, Disciplinary Parameters.